Midwifery Students' Attitudes towards Infant Feeding: A Sample from Turkey - Meltem UĞURLU (Mashhad University of Medical Sciences, 2022)
Background & aim: Midwives are the main healthcare professionals who play a critical role in supporting mothers for initiating and maintaining breastfeeding. Due to the importance of midwifery students having sufficient breastfeeding knowledge and non‐judgmental attitudes prior to graduation, this study aimed to examine the attitudes towards infant feeding of midwifery students.Methods: This survey was conducted at Health Sciences University in Ankara, Turkey in June 2021. The study was carried out on 212 midwifery students in total who agreed to take part in the study. Data was collected using the Student Information Form and IOWA Infant Feeding Attitude Scale, which were completed electronically through WhatsApp messenger and analyzed using SPSS Version 22.00.Results: The mean age of the students was 20.40±1.25. The mean score of IOWA Infant Feeding Attitude Scale was 66.18±5.52 out of 87. There was a statistically significant difference found between the mean scores of the students in the infant feeding attitude scale and their grade in school (p<0.001), receiving information in related classes (p<0.005), attending courses in the related subject (p=0.044), taking additional classes (p<0.001), and feeling themselves sufficient in terms of knowledge (p=0.009). There was no statistically significant difference with the status to give counseling.Conclusion: Midwifery students had positive attitudes towards infant feeding. It is, therefore, suggested to present an educational curriculum that supports and encourages breastfeeding in midwifery programs and to evaluate students' attitudes towards infant feeding in order to train professional midwives who will encourage families to breastfeed in the future.